THE MEANING OF WOMEN’S ROLE IN ISLAMIC EDUCATION: ANALYSIS OF SURAH AN-NISA AND THE EXEMPLARY WIVES OF THE PROPHET BASED ON USTADZ ADI HIDAYAT’S STUDY ON YOUTUBE - Satra, Alihan; Agustina, Rahma; Aldani, Muhammad Fariz; Rahmawati, Sabina; Yanti, Dewi Yuli Putri (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This article examines the role of women from an Islamic perspective by analyzing Surah An-Nisa (verses 32–34) and the exemplary character of the Prophet Muhammad’s wives, as presented in Ustadz Adi Hidayat’s lectures on YouTube. Surah An-Nisa is one of the Qur’anic chapters that explicitly addresses women's rights and responsibilities, providing a significant foundation for understanding justice and gender equality in Islam. This study aims to explore how the values contained in these verses can be applied in modern life and how figures such as Khadijah and Aisyah reflect the ideals of piety, justice, and leadership for contemporary Muslim women. Using a qualitative approach through content analysis, this research examines Ustadz Adi Hidayat’s digital religious discourse and relates it to classical interpretations and scholarly studies on women's roles in Islam. The findings suggest that Islamic teachings, through Surah An-Nisa and the exemplary lives of the Prophet’s wives, can inspire modern Muslim women to actively engage in social, educational, and leadership spheres while upholding Islamic moral and spiritual values. This study is expected to contribute to the ongoing discourse on gender in religious contexts and promote a more inclusive and contextual understanding of Islamic teachings. Artikel ini mengkaji peran perempuan dalam perspektif Islam melalui analisis Surah An-Nisa (ayat 32–34) dan karakter istri-istri Nabi Muhammad SAW, sebagaimana disampaikan dalam kajian Ustadz Adi Hidayat di platform YouTube. Surah An-Nisa merupakan salah satu surah yang secara eksplisit membahas hak dan tanggung jawab perempuan, memberikan landasan penting bagi pemahaman konsep keadilan dan kesetaraan gender dalam Islam. Artikel ini bertujuan mengeksplorasi bagaimana nilai-nilai yang terkandung dalam ayat-ayat tersebut dapat diimplementasikan dalam kehidupan kontemporer, serta bagaimana figur Khadijah dan Aisyah RA mencerminkan keteladanan perempuan Muslim dalam berbagai aspek kehidupan. Dengan menggunakan pendekatan kualitatif melalui metode analisis konten, penelitian ini mendalami narasi dakwah digital Ustadz Adi Hidayat dan mengaitkannya dengan literatur tafsir dan studi-studi ilmiah terkait peran perempuan dalam Islam. Hasil penelitian ini menunjukkan bahwa ajaran Islam melalui Surah An-Nisa dan keteladanan istri-istri Nabi mampu menjadi inspirasi bagi perempuan Muslim modern untuk berperan aktif dalam kehidupan sosial, pendidikan, dan kepemimpinan, tanpa menanggalkan nilai-nilai spiritual dan moral Islam. Temuan ini diharapkan dapat memperluas diskursus tentang gender dalam perspektif keagamaan serta mendorong pemahaman yang lebih inklusif dan kontekstual terhadap ajaran Islam.